2003
DOI: 10.1051/0004-6361:20021694
|View full text |Cite
|
Sign up to set email alerts
|

XMMNewtonobservations of the Seyfert 1 galaxy ESO 141–G55

Abstract: Abstract.We report on an observation of the Seyfert 1 galaxy ESO 141-G55 performed in October 2001 with the EPIC MOS cameras and Reflection Grating Spectrometers (RGS) on board the XMM-Newton observatory. We find the hard (3-10 keV) continuum slope, including reflection, to be somewhat flatter (Γ = 1.72 ± 0.06) than that of a typical broad-line Seyfert 1 galaxy. The spectrum shows a weak emission line at 6.45 ± 0.04 keV with a measured equivalent width of ≈40 eV. A broad spectral feature is observed around 7 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…This also explains the low to moderate ionization state of the disk. These relatively lower values are consistent with the 2001 XMM-Newton observation (Gondoin et al 2003) and other Seyfert 1s as well, e.g., Zw 229.015, where these values are log ξ = 2.56 +0.15 −0.15 erg cm s −1 and R ∼ 0.4. The iron abundance of the material in the accretion disk and the inclination of the disk to the line of sight plays an important role in describing the reflected spectra of Seyfert 1 galaxies (Crummy et al 2006;García et al 2014).…”
Section: The Soft Excesssupporting
confidence: 90%
See 1 more Smart Citation
“…This also explains the low to moderate ionization state of the disk. These relatively lower values are consistent with the 2001 XMM-Newton observation (Gondoin et al 2003) and other Seyfert 1s as well, e.g., Zw 229.015, where these values are log ξ = 2.56 +0.15 −0.15 erg cm s −1 and R ∼ 0.4. The iron abundance of the material in the accretion disk and the inclination of the disk to the line of sight plays an important role in describing the reflected spectra of Seyfert 1 galaxies (Crummy et al 2006;García et al 2014).…”
Section: The Soft Excesssupporting
confidence: 90%
“…In this work, we take a broadband spectroscopic approach to address the origin of the soft excess, the Fe K line complex and the Compton hump at E > 10 keV in the Seyfert 1 galaxy ESO 141-G055 (Elvis et al 1978) where the presence of soft excess and Fe line have been affirmatively detected by previous studies (Turner et al 1993;Gondoin et al 2003). A recent NuSTAR observation in 2016 gives us a rare opportunity to take a hard Xray (> 10 keV) look of this source.…”
Section: Introductionmentioning
confidence: 99%
“…We note that, since submission of this paper the 2000 November XMM–Newton observation of NGC 3227 has also been published by Gondoin et al (2003). They fit a slightly different model to us, we refer readers to Gondoin et al for a full discussion of their model.…”
Section: A Transient Absorption Eventmentioning
confidence: 91%
“…Although Scott et al (2004) found no significant evidence of X-ray warm absorption, this source does have an intrinsic UV absorber, making it very likely that an X-ray absorber will be found in better quality data in future; Crenshaw et al (1999) found that objects in their sample with UV absorption always showed evidence of an X-ray absorber. The one remaining object without a warm absorber, ESO 141-G55 (Gondoin et al 2003) is towards the high end of the L bol −redshift distribution, but there does not seem to be anything significantly unusual about it with respect to the other sources. NGC 4258 is basically a Seyfert 2-type object, without a soft X-ray absorber; it has however been claimed to exhibit absorption lines above 6 keV (Young & Wilson 2004).…”
Section: The Prevalence Of Warm Absorbersmentioning
confidence: 92%